Interaksi Sosial Teman Sebaya Terhadap Kematangan Emosional Siswa Kelas Delapan - Hanintya Putri Permatasari; Wiwik Kusdaryani; MA Primaningrum (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
Adolescence is considered a period of storm and stress, a time in which emotional tensions run high. Peers teach students the ability to control themselves, according to the new role they have acquired in their group. The peer environment plays a role in providing opportunities for adolescents to learn to interact and control their social behavior. The aim of this research is that the peer environment plays a role in providing opportunities for adolescents to learn to interact and control their social behavior. This research is quantitative in nature using a correlational method. The population is all class VIII students at PGRI Semarang Middle School with a total of 254 students. The sampling technique is cluster random sampling. Sampling was taken by lottery so that there were two classes selected, namely classes C and F with a total of 64 students. The instruments used in this research are the peer social interaction scale and the emotional maturity scale with four alternative answer choices. The results of hypothesis testing using the Pearson product moment correlation test, obtained a significance value of 0.000, which means that there is a relationship between Peer Social Interaction (X) and Emotional Maturity (Y). The correlation result obtained was 0.554 and was included in the medium relationship level category.